Sports management: shaping competitive performance and mass participance - Aleksandr Legotkin, Valery Panachev, Leonid Zelenin, Anatoly Opletin, (Opción, 2019)
This article introduces some measures that allow increasing the motivation to do sports, reflected by sociological research data. Polling as a sociological research method was carried out in parallel through the interview and a questionnaire. Results revealed that 46% of participants positively assess the quality of training. In conclusion, young generation has obviously a positive view of physical training. Students stand for different sports sections. Thus, educational establishments face a problem associated with their inability to deliver expectations of each student.